Transcranial Electrical Stimulation for Relief of Peripartum Mental Health Disorders in Women Undergoing Cesarean Section With Combined Spinal–Epidural Anesthesia: A Pilot Randomized Clinical Trial - Zhao, Qiu; Han, Yuan; Hu, Xiao-Yi; Zhang, Song; Zhang, Long; Wang, Jun; Zhang, Qian-Qian; Tao, Ming-Shu; Fang, Jia-xing; Yang, Jie; Liu, Rong-Guang; Sun, Xun; et al. (Frontiers in Psychiatry, 2022)
Abstract Objective: To explore tES to relieve peripartum anxiety and depressive symptoms in women undergoing caesarean section with combined spinal-epidural anesthesia. Methods: This double-blind, randomized, sham-controlled trial was conducted in the Affiliated Hospital of Xuzhou Medical University from March 2021 and May 2021. One hundred and forty-eight full-term parturients giving birth by elective caesarean section were selected and 126 were included in the intent-to-treat analysis. Parturients were provided standardized anaesthesia and randomized to active-tES (a-tES) group and sham-tES group. Parturients and outcome assessors were blinded to treatment allocation. The primary outcome was the changes in peripartum mental health disorders, including anxiety, assessed by the Pregnancy-Related Anxiety Questionnaire-Revised 2 (PRAQ-R2). Secondary outcomes included peripartum depressive symptoms, assessed by the Edinburgh postnatal depression scale (EPDS), maternal satisfaction, fatigue level, sleep quality index, pain score during and after operation. Data were collected before entering operating room (T0), between post-anesthesia and pre-surgery (T1), before leaving the operating room (T2) and on the 24 hours post-surgery (T3). Results: One hundred and twenty-six eligible parturients were enrolled in the two groups: a-tES group (N = 62) and sham-tES group (N = 64). Treatment with tES resulted in significantly lower scores of anxiety compared with sham-tES (T2: P < 0.001; T3: P = 0.001). Moreover, the a-tES groups showed significant reduction in depression scores (T2: P =0.003; T3: P = 0.032). Conclusion: In this randomized pilot study, tES treatment is efficacious in alleviating peripartum anxiety and depressive symptoms in women undergoing caesarean section and demonstrated it is a novel strategy for improving peripartum mental health disorders. Clinical Trail Registration: www.chictr.org.cn, identifier: ChiCTR2000040963.